PENERAPAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SIKAP KEMANDIRIAN PESERTA DIDIK MELALUI KEGIATAN OUTDOOR LEARNING DI SMP ISLAM CENDEKIA HARAPAN TUNGGORONO JOMBANG: PENERAPAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SIKAP KEMANDIRIAN PESERTA DIDIK MELALUI KEGIATAN OUTDOOR LEARNING DI SMP ISLAM CENDEKIA HARAPAN TUNGGORONO JOMBANG - Puistin Nirwani Azizah; Laily Masruroh (CV. ALIM'SPUBLISHING, 2024)
Education is a basic need that humans need. Education is an effort in the form of teaching, training and guidance to prepare students for the future. Islamic religious education is a subject developed from the basic teachings of the Islamic religion. Based on the problems above, this research has 3 objectives related to the research focus of the Application of Islamic Religious Education Values ​​in Improving Students' Independent Attitudes Through Outdoor Learning Activities at the SMP Islamic Cendekia Harapan Tunggorono Jombang. The aim of the research is to describe the application of PAI values ​​in increasing students' independent attitudes, describe the application of PAI values ​​in increasing students' independent attitudes through outdoor learning activities, supporting and inhibiting factors. In this research, researchers took a qualitative research method approach. In this research the researcher took the type of field research and descriptive research. Data collection was carried out using interviews, observation and documentation. In general, according to the opinion of the resource person above, the inhibiting factors are facilities, the condition of students, and a community environment that is less supportive. Broadly speaking, the supporting factors are the support of students and foundations.